C-, N-Vacancy defect engineered polymeric carbon nitride towards photocatalysis: viewpoints and challenges. Issue 1 (8th December 2020) - Kumar, Abhinandan; Raizada, Pankaj; Hosseini-Bandegharaei, Ahmad; Thakur, Vijay Kumar; Nguyen, Van-Huy; Singh, Pardeep
Abstract : As an alluring metal-free polymeric semiconductor material, graphite-like carbon nitride (g-C3 N4 ; abbreviated as GCN) has triggered a new impetus in the field of photocatalysis, mainly favoured from its fascinating physicochemical and photoelectronic structural features. Abstract : As an alluring metal-free polymeric semiconductor material, graphite-like carbon nitride (g-C3 N4 ; abbreviated as GCN) has triggered a new impetus in the field of photocatalysis, mainly favoured from its fascinating physicochemical and photoelectronic structural features. However, certain inherent drawbacks, involving rapid reassembly of photocarriers, low specific surface area and insufficient optical absorption, limit the wide-range applicability of GCN. Generation of 0D point defects mainly by introducing vacancies (C and/or N) into the framework of GCN has spurred extensive consideration owing to their distinctive qualities to manoeuvre substantially, the optical absorption, radiative carrier isolation, and surface photoreactions. The present review endeavours to summarise a comprehensive study on vacancy defect engineered GCN. Starting from the basic introduction of defects and C/N vacancy modulated GCN, numerous advanced strategies for the controlled designing of vacancy rich GCN have been explored and discussed. Afterwards, light was thrown on the various substantial technologies which are useful for characterising and identifying the introduction of defects in GCN. The salient significance of defect engineering in GCN has been reviewed concerning its impact on optical absorption, charge isolation and surface photoreaction ability. Typically, the achievement of defect engineered GCN has been scrutinised toward various applications like photocatalytic water splitting, CO2 conversion, N2 fixation, pollutant degradation, and H2 O2 production. Finally, the review ends with conclusions and vouchsafing future challenges and opportunities on the intriguing and emerging area of vacancy defect engineered GCN photocatalysts.